Analisis Bibliometrik Kajian Literasi Petani: Implikasi bagi Pengembangan Sumber Daya Informasi di Perpustakaan Pertanian - Mohamad Hasan As'Adi; Abdul Riski (Media Informasi, 2026)
The increase in publications on farmer literacy in the last four decades shows significant academic attention to information capacity and technological adaptation in the agricultural sector. However, this growth has not been accompanied by comprehensive mapping that can identify the intellectual architecture, global collaboration patterns, and its strategic implications for the development of agricultural library services. Ideally, information institutions need data-based synthesis to design collections, partnership networks, and literacy programmes that are responsive to scientific dynamics. This research aims to fill this gap through bibliometric analysis of 978 publications indexed in Scopus for the period 1984–2024 using Biblioshiny. The research results show that the study of farmer literacy experiences an annual growth rate of 13.8%, dominance of journal articles (77.4%), and concentration of contributions in China, the United States, and Australia. The thematic evolution shows a shift from general agricultural literacy towards digital, financial, and environmental literacy integrated with technological transformation. The network analysis reveals clustered collaboration patterns with strategic linking actors in global knowledge circulation. The findings of this research provide an empirical foundation for strengthening agricultural libraries as adaptive and networked knowledge nodes.